2020
DOI: 10.1007/s12132-020-09400-w
|View full text |Cite
|
Sign up to set email alerts
|

The City and the Barracas: Urban Change, Spatial Differentiation and Citizenship in Maputo

Abstract: The paper discusses Maputo municipality's plans for the modernisation of the Mercado do Museu, an iconic informal market located in the high-end Polana neighbourhood, which has long been a place for fervent social encounter among people from different social and economic origins. The Mercado's upgrading plans emerge within the context of Maputo's intensely urban transformation that has led gentrification effects, especially in the city's wealthiest areas. This stems partly from private real estate investment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…Similarly, in Kumasi (Ghana), low-income residents were displaced to the city's periphery, and traditional buildings were demolished rather than refurbished or remodelled (Twumasi & Oppong, 2016;Cobbinah et al, 2019). This trend could also be observed in Maputo, with the municipality's plan for modernisation partly enabled by private real estate investment and partly by extensive infrastructure and housing projects promoted by the Mozambican state (Roque et al, 2020). This has also been the case in the capital of Ethiopia, Addis Ababa (Nunzio, 2022) and Kigali in Rwanda (Shearer, 2020).…”
Section: Tourism Gentrification and Its Various Manifestationsmentioning
confidence: 98%
“…Similarly, in Kumasi (Ghana), low-income residents were displaced to the city's periphery, and traditional buildings were demolished rather than refurbished or remodelled (Twumasi & Oppong, 2016;Cobbinah et al, 2019). This trend could also be observed in Maputo, with the municipality's plan for modernisation partly enabled by private real estate investment and partly by extensive infrastructure and housing projects promoted by the Mozambican state (Roque et al, 2020). This has also been the case in the capital of Ethiopia, Addis Ababa (Nunzio, 2022) and Kigali in Rwanda (Shearer, 2020).…”
Section: Tourism Gentrification and Its Various Manifestationsmentioning
confidence: 98%
“…A precariedade (ou até mesmo, completa ausência) de muitas infraestruturas e serviços públicossistemas de transporte, saúde, educação e segurança; oferta de água, eletrificação, pavimentação, saneamento básico, iluminação e coleta de lixo -caracterizam esta porção do território municipal e revelam a difícil realidade que agoniza a vida de grande parcela dos maputenses. Roque, et al (2020) indicam que, embora essa porção do território urbano tenha se (re)produzido de maneira informal -pelos próprios moradores -o governo municipal insiste em vê-la como uma expressão de um urbano incompleto (ou inadequado). Por trás desta concepção, têm-se raízes históricas da realidade colonial, período em que a "cidade de caniço" era considerada "reserva de terras" para futuras expansões da "cidade de cimento".…”
Section: A "Cidade De Caniço": Segregação Desemprego E Misériaunclassified
“…A concepção de um "urbano incompleto" -de moradias temporárias edificadas em materiais instáveis -por vezes, tem sido aplicada numa perspectiva "higienista". Narrativas de desordem, ilegalidade poluição são empreendidas para legitimar ações de despejo ou remanejamentos que possibilitem a efetivação destes de novos projetos (ROQUE et al, 2020).…”
Section: A "Cidade De Caniço": Segregação Desemprego E Misériaunclassified
“…Mozambican history has revealed that a series of internal episodes have contributed to the collapse of the, which is already weakened, organizational and economic structure of the country. In a span of only three decades (1970/80/90), Mozambique has faced crises of internal shortages, falling agricultural and industrial production, civil war, independence struggle, short experience with the socialist regime, liberalization of the economy, introduction and intervention of the International Monetary Fund (IMF) and World Bank (WB) programs, among others (SILVA, 2002;CHIVANGUE, 2014;ROQUE et al, 2020).…”
Section: The "Reed City": Segregation Unemployment and Miserymentioning
confidence: 99%
“…The concept of an "incomplete urban", of temporary housing built in unstable materials, has sometimes been applied from a "hygienist" perspective. Narratives of disorder, illegality, and pollution are constantly used to legitimize eviction or relocation actions that enable the implementation of new projects (ROQUE et al, 2020).…”
Section: (Re)qualification Projects Real Estate Speculation and The I...mentioning
confidence: 99%